2019
DOI: 10.3390/agronomy9120889
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Conservation and Use of Traditional Germplasm through Breeding for Local Adaptation: The Case of the Castellfollit del Boix Common Bean (Phaseolus vulgaris L.) Landrace

Abstract: The dramatic reduction in the diversity of crops in the last century is often attributed to the consolidation of scientific breeding, probably because the two processes have occurred at the same time. We carried out a breeding program to enhance the Castellfollit del Boix landrace of common bean (Phaseolus vulgaris L.) in a low-input environment to determine the effects of breeding on a landrace at risk of disappearing. The program increased the number of accessions conserved ex situ and obtained more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…They concluded that, given the particular economic returns, it is worth continuing to invest in research in this species. Casals et al (2019) carried out a study on the common bean (P. vulgaris) to help conserve genetic variability, avoid erosion and guarantee adaptation processes to changes in the climate and the environment.…”
mentioning
confidence: 99%
“…They concluded that, given the particular economic returns, it is worth continuing to invest in research in this species. Casals et al (2019) carried out a study on the common bean (P. vulgaris) to help conserve genetic variability, avoid erosion and guarantee adaptation processes to changes in the climate and the environment.…”
mentioning
confidence: 99%
“…On the other hand, local varieties of vegetables have been associated to the "taste of the past" (Casals et al, 2011;Causse et al, 2010). In this way, they have been reported to produce more flavourful, nutritious fruits than modern varieties in several studies (Casals et al, 2019a;Celmeli et al, 2018;Cortés-Olmos et al, 2014;Medina-Lozano and Díaz, 2021;Meza et al, 2020;Parisi et al, 2017;Sánchez et al, 2018). For instance, the Almagro eggplant landrace showed higher values for protein, vitamin C, glucose and total phenolics compared to commercial cultivars in San .…”
Section: Local Varieties As Source Of Variationmentioning
confidence: 99%